Encoding Culture, Embodying Identity: A Study of Somatic Proverbs - Nurutdinova, Aida R. (Cross-Cultural Education Studies, 2026)
This article presents a cross-cultural investigation into somatic paroemias (proverbs and idioms structured by bodily imagery) positioning them as fundamental linguistic expressions that encapsulate a culture’s embodied memory and actively shape conceptions of national identity. By integrating an analytical methodology that couples corpus linguistics with conceptual metaphor theory, the study delineates the implicit, body-based cognitive schemas structuring proverbial language across Russian, English, and Japanese. The methodology synthesizes quantitative pattern identification from corpus data with qualitative conceptual analysis, further enriched by insights from gesture ethnography and phenomenological theory to establish the lived, experiential grounding of these linguistic forms. Through this triangulated approach, the research identifies three distinct cultural templates: the Russian logic of vertical ascent and descent frequently linked to the SOUL; the Anglo-American model of internal containment, centred on the HEART and GUT; and the Japanese principle of abdominal centrality HARA and fluid integration. The findings demonstrate how these proverbial patterns function not merely as figurative speech but as cognitive repositories of sedimented, “frozen” lived experience, preserving historical bodily dispositions in transmissible form. Consequently, the study argues that this proverbial layer constitutes a crucial mechanism for the tacit, communal transmission of corporeal identity, serving as a vital bridge between universal human physicality and culturally specific meaning systems. Engaging analytically with this embodied dimension of language thus offers a profound pathway for deepening our understanding of how collective identity is intuitively formed, mnemonically sustained, and phenomenologically differentiated across cultures.